In the Eye of the BBHolder: A Look into Recent Trends in Blood Bank Hold Order Utilization. (28th October 2020) - Hensley, Marie; Pagano, Monica; Mathias, Patrick
Abstract: The transfusion service at a large academic institution provides transfusion support to the regional cancer center in inpatient and outpatient settings. This center has a large patient population many of whom require frequent blood count monitoring. To reduce the number of blood draws and port accesses, it is standard of care to collect a blood bank hold (BBHold) tube simultaneously with routine CBC samples. The BBHold tube is routed to the transfusion services lab and stored in case a type and crossmatch (TXM) is needed in preparation for transfusion; it is valid for 72 hours. While advantages to this system are eliminating the need for a secondary blood draw and ready access to a sample for transfusion testing, disadvantages include drawing an additional tube, increased cost and storage, and increased specimen mislabeling in the conversion of a BBHold to a TXM. Our objectives were to analyze trends in BBHold usage, make recommendations to reduce unnecessary utilization, and create an algorithm to predict which patients would need transfusion. We collected data from March 2016 to June 2019 including hemoglobin values, BBHold orders, and TXM orders, and used the statistical programming language R for data analysis. Approximately 1, 000 BBHold samples were collected monthly, with 64.2% taking place in the outpatient setting. Our analysis focused on this outpatient population. A total of 31.1% of BBHold orders were unnecessary, as they were re-collected within the 72-hour window of sample viability. Of all the BBHold orders, including the previously mentioned unnecessary orders, only 32.7% were converted to a TXM, which was used as a surrogate marker for transfusion. Unexpectedly, 28.2% of the last hemoglobin values collected prior to a BBHold (either concurrently with the BBHold or up to 3 days prior) were ≥10 g/dL. Notably, only 44.6% of these hemoglobin orders occurred concurrently with a BBHold, indicating that over 55% of BBHold orders were placed after the hemoglobin order. Once a hemoglobin value is resulted, a BBHold has minimal use since the hemoglobin value would determine if a transfusion is indicated. If transfusion is indicated, a TXM order should be placed directly, rather than a BBHold. Next, the average hemoglobin values were compared between patients who did and did not receive a transfusion within 7 days, and these were 8.8 and 9.1 g/dL, respectively. In conclusion, the trends illustrated here indicate overutilization of BBHold orders and highlight potential areas for optimization. Hemoglobin values within 7 days of a BBHold may not be enough to design a robust algorithm to stratify patients based on need for transfusion. Recommendations moving forward may include improving the EHR interface to display the expiration date of the current BBHold sample or displaying the patient's last hemoglobin if ≥10 g/dL.